Depression, anxiety, stress and its correlates among urban school going adolescents in Tamilnadu, India - Daya A., Praveena; G., Karthikeyan (International Journal of Research in Medical Sciences, 2018)
Background: Undetected and untreated mental disorders can impair a person’s ability to perform at school or work place, cope with daily activities of life and can lead to severe psychiatric disorders and consequences later in their life. Study objective was to determine the prevalence and patterns of depression, anxiety and stress among 400 school going adolescents belonging to classes 10th to 12th of Tirunelveli district, Tamilnadu, India. Methods: Burden of Depression, anxiety and stress was assessed using DASS21 questionnaire. Chi-square test was done using SPSS software version 21 to test for statistical significance. Results: Overall prevalence of depression, anxiety and stress was 73.6%, 86.5% and 24.7% respectively. Depression (p value=0.01), Anxiety (p value = 0.005) and stress (p value = 0.007) were significantly observed more among 10th class students when compared with other classes. Conclusions: The present study has identified a higher prevalence of depression, anxiety and stress among students. This warrants immediate action of creating awareness among teachers and parents in early identification and treatment to prevent serious consequences in later life.